The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1042/bj3550237
|View full text |Cite
|
Sign up to set email alerts
|

(S)-Preferential detoxification of 4-hydroxy-2(E)-nonenal enantiomers by hepatic glutathione S-transferase isoforms in guinea-pigs and rats

Abstract: In guinea-pig liver cytosol, racemic 4-hydroxy-2(E)-nonenal (HNE), a reactive and highly toxic product released from biomembranes by lipid peroxidation, was detoxified (S)-preferentially by GSH conjugation mediated by glutathione Stransferases (GSTs) and (R)-preferentially by NAD + -dependent oxidation mediated by aldehyde dehydrogenase (ALDH). The GST-mediated detoxification of the HNE enantiomers proceeded at much higher rates than that mediated by ALDH in guinea-pig liver cytosol. All the major guinea-pig G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…However, the total activity of GSTs in the liver did not differ significantly between the control and DHA-fed groups (Table 2). Ålin et al [34] and Hiratsuka et al [35] reported that GSTA4-4, which present as a very minor GST protein in rat liver, exhibited extremely high catalytic activity towards 4-HNE. When GSTs in rat liver were separated by the chromatography on DEAE-cellulose column, GST A4-4 (also called GST 8-8) activity (60 µmol/min) was much lower than other GSTs activity (4460 µmol/min) [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, the total activity of GSTs in the liver did not differ significantly between the control and DHA-fed groups (Table 2). Ålin et al [34] and Hiratsuka et al [35] reported that GSTA4-4, which present as a very minor GST protein in rat liver, exhibited extremely high catalytic activity towards 4-HNE. When GSTs in rat liver were separated by the chromatography on DEAE-cellulose column, GST A4-4 (also called GST 8-8) activity (60 µmol/min) was much lower than other GSTs activity (4460 µmol/min) [34].…”
Section: Discussionmentioning
confidence: 99%
“…The alphaand Mu-class rat GSTs catalyze GS-HNE preferentially. 40) Of the Mu-class rat GSTs, M2-2 is the most efficient. 40) However, there was no significant change in the expression of GST M2 mRNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hiratsuka et al (32) demonstrated that the S-HNE enantiomer irreversibly inactivated rabbit glyceraldehyde-3-phosphate dehydrogenase at a greater rate than R-HNE. They also found a stereoselective consumption of substrate by rat GSTA4-4 in the order of S-HNE Ͼ racemic HNE Ͼ R-HNE (33), whereas a separate study by Boon et al (28) speculated that product stereoselectivity on behalf of GSTs is one potential explanation for the unequal distribution of GSHNE diastereomers observed in rat liver cytosol. Chirality has also been implicated as an important factor in other enzymes, such as aldehyde-dehydrogenase and aldo-keto reductases, that can also contribute to HNE metabolism and subsequent biotransformations of GSHNE (34 -36).…”
mentioning
confidence: 96%